Only two subscales of the Coping Strategies Questionnaire are culturally relevant for people with chronic low back pain in Nigerian Igbo populations: a cross-cultural adaptation and validation study - Chinonso Nwamaka Igwesi-Chidobe; Isaac Olubunmi Sorinola; Emma Louise Godfrey (SpringerOpen, 2021)
Abstract Background Pain coping strategies are important in the chronicity of low back pain and the associated disability. However, their exact influence is unknown in many African contexts such as rural Nigeria due to lack of outcome instruments with which to measure them. This study aimed to cross-culturally adapt and psychometrically test the Coping Strategies Questionnaire (CSQ) in Igbo populations in Nigeria. Methods The CSQ was forward and back translated by clinical and non-clinical translators; evaluated by an expert review committee. The translated measure was piloted amongst twelve rural Nigerian dwellers with chronic low back pain (CLBP) using the think-aloud cognitive interviewing style. Internal consistency (Cronbach's alpha), test-retest reliability (intra-class correlation coefficient-ICC and Bland-Altman plot), and minimal detectable change were examined amongst 50 people with CLBP in rural and urban Nigerian populations. Construct validity was determined by assessing the correlations between the adapted CSQ and measures of disability, pain intensity, fear avoidance beliefs, and illness perceptions using Spearman's correlation analyses with 200 adults with CLBP in rural Nigeria. Exploratory factor analyses using Kaiser criterion (eigenvalue) and parallel analysis as methods for determining dimensionality were conducted with the same sample. Results Fourteen out of 42 items were routinely adopted in this population including all items of catastrophising subscale, and all but one item of praying and hoping subscale. Catastrophising and praying and hoping subscales had the highest Cronbach's alpha. All subscales had high ICCs with Bland-Altman plots that showed good agreement. All coping strategies were positively correlated with self-reported disability and pain intensity with catastrophising subscale having the highest values. Seven-factor and three-factor structures were produced with the Kaiser criterion and parallel analysis, with different items from the original CSQ, except for catastrophising. Conclusions Catastrophising and praying and hoping may be the relevant coping strategies in this population. More culturally relevant measures of pain coping strategies that include adaptive coping strategies may need to be developed for African contexts such as rural Nigeria.